Pengaruh Supervisi Kepala Sekolah dan Kompetensi Pedagogik Guru terhadap Kinerja Guru di SMAN 1 Kisam Tinggi - Septiyana, Etika (Journal of Innovation in Teaching and Instructional Media, 2022)
The purpose of this study was to determine the effect of principal supervision and teacher pedagogic competence on teacher performance at SMAN 1 Kisam Tinggi. The type of research used is descriptive analysis with a quantitative approach to see the effect of the principal's supervision variable and the teacher's pedagogic competence variable on the teacher's performance variable through hypothesis testing. This study uses a questionnaire that is relevant to all variables as a data collection tool. The questionnaire used is 5 Likert scale, and has been tested for validity and reliability test. The sample in this study were all 30 teachers at SMAN 1 Kisam Tinggi. This research uses simple regression data analysis method and multiple regression. The results showed that the principal's supervision partially affected the performance of teachers at SMAN 1 Kisam Tinggi. The teacher's pedagogic competence partially influences the performance of teachers at SMAN 1 Kisam Tinggi. Principal supervision and teacher pedagogic competence simultaneously affect teacher performance at SMAN 1 Kisam Tinggi. Based on the value of the coefficient of determination test results, 82.2% of teacher performance can be explained by the supervision of the principal and pedagogic competence, meaning that there is a contribution of 82.2% given the supervision of the principal and pedagogical competence on teacher performance, and the remaining 17.8% (100%-82.2%) of the teacher's performance can be explained by other reasons.